Prevalence and Risk Factors of SARS-CoV-2 Among Patients with Suspected Respiratory Infections at Specialist Hospital, Gombe State, Nigeria - Bello Yakubu, Adamu; Ibrahim, Zuhairu; Yakubu, Adamu; Mohammed, Muhammed Musa; Adamu, Aliyu; Auwal, Abdullahi; Mustapha, Ibrahim; Kwaau, Nathaniel Luka; Muhammad, Bashir; Bile, Nuhu; Saleh, Rakiya; Abubakar, Bashir Mohammed; et al. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
The novel corona virus (SARS-CoV-2) has quickly spread from person to person and claimed millions of lives worldwide. However, there is a lack of epidemiological data on this infectious agent in Gombe State. This study aimed to determine the prevalence of SARS-CoV-2 and its associated risk factors among patients with suspected respiratory infections attending the General Hospital in Gombe State, Nigeria. Approximately 200 nasopharyngeal and/or oropharyngeal samples were collected from participants across Gombe State and screened for COVID-19 using Rapid Diagnostic Kits (RDT). In addition, Semi-structured questionnaires were used to collect additional demographic data. The data were analyzed statistically using SPSS version 22. The results indicated an overall prevalence rate of 26.5%. Chi-square analysis showed that demographic factors such as gender, age, location, and educational background were significantly associated with COVID-19 infection, while tribe and occupation were found to be statistically insignificant. Additionally, binary and multiple logistic regression analyses identified male sex, adult age, urban residence, and lower education levels as significant risk factors for COVID-19 infection. Therefore, this study recommends the implementation of a vaccination program to help contain the spread of SARS-CoV-2 infection.